Restoration of Intestinal Propulsion in Patients with Severe Acute Pancreatitis in the Conditions of the Resuscitation and Intensive Care Unit - V. V. Kiselev; S. S. Petrikov; M. S. Zhigalova; S. V. Novikov; N. V. Shavrina; P. A. Yartsev (Неотложная медицинская помощь, 2023)
The intestine plays an important role in the processes of systemic inflammation, sepsis and multiple organ dysfunction, in the course of hemorrhagic shock, trauma, burns, pancreatitis, extensive abdominal surgery and in seriously ill patients in intensive care units (ICUs). One of the leading causes affecting the outcomes of treatment of surgical patients after interventions on the abdominal organs continues to be the syndrome of intestinal insufficiency developing in the early postoperative period, which important pathogenetic aspect is impairment of the propulsive function of the intestine.AIM OF THE STUDY Improving treatment outcomes in patients with severe acute pancreatitis by restoring propulsive bowel function.MATERIAL AND METHODS The study included 94 patients with severe acute pancreatitis (67 (71.3%) men and 27 (28.7%) women) admitted to the ICU in the first 24–72 hours from the onset of the disease (abdominal pain syndrome). The mean age was 48.2 ± 12.5 years, the patients were divided into two study groups: patients of the comparison group (n=40) received standard therapy in the ICU, patients of the study group (n=54) described treatment was supplemented with the use of saline enteral solution and early start of enteral nutrition in order to restore the functional activity of the intestine.RESULTS Extended therapy with the inclusion of saline enteral solution made it possible to correct the manifestations of intestinal failure syndrome 2.4 times faster, to start enteral nutrition on day 2.1±0.8 of dynamic observation in the ICU in patients of the study group, which contributed to leveling the manifestations of intestinal failure syndrome, prevention and treatment of nutritional deficiencies. At the same time, effective intestinal peristalsis, confirmed by ultrasound, was determined in 57.4% of patients on day 2.1±1.6, in 35.1% on day 3.6±2.0, in 7.4% of patients on day 4.8±1.7 of stay in the ICU. While in the comparison group, peristalsis was determined in 37.5% of patients in 4.4±2.3 days, in 30% of patients in 6.2±1.1 days, in 27.5% in 8.1±3.6 days, in 5% of patients in 10.4±2.2 days and in 6.7% of patients it was not possible to restore effective peristalsis.CONCLUSION Enteral solution in the treatment regimen for patients with a diagnosis of “Acute severe pancreatitis” contributed to a more rapid recovery of the effective motor-evacuation function of the intestine and made it possible to reduce the number of purulent-septic complications 1.4-fold, cases of multiple organ failure 1.7-fold, and mortality 1.6-fold.